Impact of pancreatectomy on long‐term patient‐reported symptoms and quality of life in recurrence‐free survivors of pancreatic and periampullary neoplasms. Issue 2 (11th November 2016) - Cloyd, Jordan M.; Tran Cao, Hop S.; Petzel, Maria Q.B.; Denbo, Jason W.; Parker, Nathan H.; Nogueras‐González, Graciela M.; Liles, Joseph S.; Kim, Michael P.; Lee, Jeffrey E.; Vauthey, Jean‐Nicolas; Aloia, Thomas A.; Fleming, Jason B.; et al.
Abstract : Background: Long term patient‐reported symptoms and quality of life (QOL) are important outcome metrics following cancer operations, but have been poorly described in patients who have previously undergone pancreatectomy. Methods: We conducted a cross‐sectional survey of recurrence‐free survivors of pancreatic ductal adenocarcinoma, periampullary carcinomas, and pancreatic neuroendocrine tumors who had undergone prior pancreatectomy. QOL and symptom burden were measured using the Functional Assessment of Cancer Therapy–Hepatobiliary Questionnaire, and psychosocial distress was measured using the Hospital Anxiety and Depression Scale. Results: Of 331 eligible patients surveyed, 217 (66%) participated at a median of 53.3 (range, 7.6–214.8) months following pancreatoduodenectomy (PD, n = 165) or distal pancreatectomy (DP, n = 52). Among all patients, overall QOL scores were favorable and influenced by race, histology, and type of surgery. The most common significant symptoms reported were fatigue (82%), back pain (32%), and difficulty with digestion (31%). In general, PD survivors reported better QOL, lower levels of anxiety/depression, greater levels of diarrhea, and improved appetite, constipation, fatigue, anxiety, and depression ( P  < 0.05) than DP survivors. On both univariate and multivariate regression analysis, DP was negatively associated with QOL. Conclusions: Most disease‐free survivors of pancreatic neoplasms report favorable QOL, but gastrointestinal and psychosocial symptoms may exist long after pancreatectomy. J. Surg. Oncol. 2017;115:144–150 . © 2016 Wiley Periodicals, Inc.